COMPARISON OF CARTILAGE TYPE IIIA AND IIIB TYMPANOPLASTY IN INDIAN PATIENTS WITH CHRONIC SUPPURATIVE OTITIS MEDIA - Reddy, Prashant R; Vuppala, Rakesh; Bhat, Supriya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This prospective comparative study determined the efficacy of type III tympanoplasty using homologous septal spur cartilage in patients with chronic otitis medis (COM). Methods: We selected patients by random sampling. Complete otolaryngologica examination including otological examination, tuning fork tests, pure tone audiometry (PTA), and relevant investigations was done. Post-tympanoplasty residual air-bone gap (ABG) was graded. Type III tympanoplasty was done for all and followed up until month 6. Results: Of 50 patients, 70.0% were men. Mean age was 27.72±10.81 years, 24 and 26 patients underwent type IIIA and IIIB tympanoplasty, respectively. Pre-operative mean PTA and ABG was 50.08 dB and 38.27 dB, respectively. Pre-operative ABG of 31–60 dB was seen in 41 patients while nine had an ABG of 0–30 dB. Overall, pre- and post-operative PTA was 50.24 dB and 28.54 dB, respectively. Overall, pre- and post-operative ABG was 38.32 dB and 16.40 dB (III A 36.92 dB and 14.79 dB; III B 39.62 dB and 17.88 dB). Mean overall hearing gain postoperatively in PTA was 21.70 dB (type III A 22.33 dB, III B −21.115 dB). Overall, ABG closure was 23.53 dB (type III A 22.333 dB, III B −21.115 dB). None had failure (>30 dB). Good ABG of 10–20 dB was seen in 72% and 78% of patients at month 3 and 6, respectively. Conclusion: Significant post-operative hearing improvement was seen in both types of tympanoplasty using homologous cartilage graft for ossicular reconstruction. Type III A is better than type IIIB as the stapes superstructure is vital for hearing.